Phosphorus HotSpots in Crop Plants Production on the Farm—Mitigating Critical Factors - Witold Grzebisz; Alicja Niewiadomska; Jarosław Potarzycki; Agnieszka Andrzejewska (Agronomy, 2024)
Phosphorus resources, both in phosphate rocks and in the soil, are limited. However, effective food production is not possible without the use of P fertilizers. Recognizing and eliminating or at least ameliorating factors (hot spots) that interfere with the uptake and use of phosphorus (P) by crop plants is of key importance for effective use of both P and nitrogen (N) on the farm. Plants have developed many adaptation mechanisms to their environment, i.e., soil low in available phosphorus. The most important ones include the secretion of organic compounds into the rhizosphere and the association of plant roots with microorganisms. A classic example is mycorrhiza. These mechanisms can be used by the farmer to sequentially select plants in the crop rotation. The uptake of inorganic P (Pi) by plants from the soil is reduced by environmental (temperature and water) and soil factors (low content of available phosphorus, soil acidity, soil compaction). These factors are responsible for the growth and size of the root system. Mitigating these negative effects improves the efficiency of phosphorus uptake from the soil. The second group of critical factors, limiting both root growth and availability of phosphorus, can be effectively controlled using simple measures (for example, lime). Knowing this, the farmer must first control the level of soil fertility in the plant’s effective rooting zone and not only in the topsoil. Secondly, the farmer must multiply the productivity of applied mineral fertilizers used through targeted recycling: crop rotation, crop residues, and manure.